Stunting as a Health Problem in Developing Countries: A Systematic Literature Review - Yuliarni; Shelly Juliska; Rizka Amayu; Merry Afriliana Sari; Muhammad Alamsyah; Ahmad Azwin Fadhlan; Hamzah Hasyim (Community Medicine and Education Journal, 2023)
Stunting, or stunted growth in children, is a serious public health problem in developing countries. The risk factors that contribute to the prevalence of stunting in these countries are complex and multifactorial. In an effort to understand this problem, this study aimed to present a number of risk factors associated with stunting in children in developing countries. Preparing this literature review begins with searching journals, articles, and scientific works through a search engine like Google Scholar and PubMed using the keywords "stunting", "stunting prevalence", "stunting risk factors", "stunting prevention", and "developing countries". The prevalence of stunting cases is still quite high in developing countries. Risk factors for children and mothers play a significant role in the incidence of stunting in children in developing countries. The factors of birth weight, child's age, gender, mother's education level, and family welfare act as the main factors in initiating stunting.